A method for preparing and in-situ observing a laser cladding interface micro-tensile fracture sample
Patent Information
- Application Number
- CN202611389747.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-13
AI Technical Summary
[0004]然而,上述传统方式在实际工程应用中存在诸多难以克服的缺陷与弊端
1.选用扫描电子显微镜仓内的微区显微拉伸台进行原位观测,能够实时且连续地记录裂纹萌生、扩展至最终断裂的完整微观形貌演化过程,为分析界面失效机制以及探究激光熔覆物理过程提供了真实可靠的试验手段,突破了传统宏观拉伸测试中无法捕获微观动态断裂特征的瓶颈。
Smart Images

Figure CN122900936A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of surface modification of metallic materials and material performance testing technology, and in particular to a method for preparing and in-situ observing microscopic tensile fracture specimens at laser cladding interfaces. Background Technology
[0002] In the field of surface modification technology for metallic materials, laser cladding technology serves as a core method. It utilizes a high-energy heat source to metallurgically fuse the cladding material with the substrate surface, resulting in rapid solidification and the formation of a high-performance cladding layer. However, due to the high solidification rate and large residual stress gradient, the internal microstructure and mechanical properties of the fusion interface region between the cladding layer and the substrate often exhibit transitional and abrupt changes. This makes it a vulnerable area prone to failure during actual service loading, directly limiting the overall service life of the component. To deeply investigate the failure mechanism, crack propagation path, and interfacial bonding strength of the fusion interface, it is necessary to obtain high-quality, defect-free test specimens and capture the entire evolution of interfacial fracture in situ without damaging the original microstructure. This has become a key requirement for performance evaluation and physical process investigation of modified workpieces.
[0003] To address this testing requirement, the traditional solution typically involves using a conventional universal tensile testing machine for macroscopic mechanical tensile testing. Furthermore, to prepare test specimens that meet conventional macroscopic tensile standards, traditional processes often require multi-layer, multi-pass laser cladding to continuously stack and additively manufacture materials on the substrate surface to achieve the required thickness. Regarding the observation of the fracture process at the microscopic level, existing conventional testing methods involve directly clamping and fixing the microscopic specimen on a micro-tense stage, applying tensile loading at a fixed speed under a microscope, and recording the process morphology using image acquisition software.
[0004] However, the aforementioned traditional methods have many insurmountable defects and drawbacks in practical engineering applications. First, universal tensile testing machines can only perform destructive loading at the macroscopic scale. The fusion interface often fractures instantaneously under macroscopic tensile force, and traditional testing methods cannot capture the continuous microscopic dynamic evolution of interface cracks from incubation to propagation. Second, the thickness of a single-layer thin cladding layer in laser cladding is usually very limited. Forcibly using multi-layer, multi-pass cladding processes to stack the thickness to meet macroscopic dimensions easily introduces multiple microscopic cracks and porosity defects inside the sample, damaging the inherent metallurgical quality of the test sample itself and causing a large waste of substrate and cladding powder materials, resulting in high preparation costs. Finally, the minimum tensile speed of commercially available micro-area micro-tensile stages is usually fixed and relatively high, which is not matched with the actual service stress rate of the cladding interface. The excessively high tensile speed causes microscopic crack propagation to be completed instantaneously, making it impossible for microscopic image acquisition equipment to capture key stage fracture morphology images, ultimately leading to serious distortion of observation and mechanical analysis results. Summary of the Invention
[0005] To address the aforementioned issues, this invention provides a method for preparing and in-situ observing microscopic tensile fracture specimens at laser cladding interfaces. The method employs a grooved substrate with a pre-defined rectangular groove for single-layer, multi-pass laser cladding to construct a clad part containing a fusion interface. Based on the target shape characteristics, a microscopic tensile specimen with a notch in the middle related to the fusion interface is cut out. In-situ loading is performed using a discontinuous tensile strategy that alternates between tensile and load-holding actions on a micro-area micro-tensile stage. This method overcomes the limitations of single-layer cladding thickness and reduces material costs, while simultaneously capturing the complete microscopic evolution process of crack initiation, propagation, and fracture at the laser cladding fusion interface.
[0006] The above objectives can be achieved through the following approach: A method for preparing and in-situ observing microscopic tensile fracture specimens at laser cladding interfaces includes: extracting load range parameters and dimensional requirement parameters of a microscopic in-situ tensile testing device, and extracting tensile property data of the material to be tested; constructing target size feature data and target shape feature data of the microscopic tensile specimen based on the load range parameters, the dimensional requirement parameters, and the tensile property data; performing wire cutting on the substrate surface based on the target size feature data to output a grooved substrate with a preset rectangular groove; cleaning the preset rectangular groove of the grooved substrate, and performing a single-layer multi-pass laser cladding operation on the cleaned grooved substrate to guide the cladding material to bond with the sidewall of the preset rectangular groove, generating a clad part containing a laser cladding layer and a fusion interface; and performing laser cladding on the target shape feature data. The cladding component undergoes a positioning and cutting action to output a microscopic tensile specimen for testing. The specimen has a notch at its center associated with the fusion interface. A clamping device is controlled to assemble the specimen into a micro-area tensile stage within a scanning electron microscope, and a device configuration action is performed based on preset maximum load parameters and preset imaging frequency parameters. The micro-area tensile stage is controlled to perform tensile testing on the specimen using an intermittent tensile strategy that alternates between tensile and load-holding actions, and load-displacement curve data and microscopic fracture process image data are simultaneously extracted using the scanning electron microscope. Based on the load-displacement curve data and microscopic fracture process image data, mechanical and morphological analysis actions are performed, outputting interface mechanical property data and interface fracture failure mode data.
[0007] Optionally, constructing target size feature data and target shape feature data of the microscopic tensile specimen based on the load range parameter, the size requirement parameter, and the tensile property data includes: extracting the required fracture load parameter based on the tensile property data; adjusting the cross-sectional thickness value so that the fracture load parameter matches a preset proportional node of the load range parameter; constructing assembly positioning hole feature data on both sides based on the size requirement parameter; and constructing notch feature data in the middle position based on the fracture load parameter, so as to constrain the fracture position to be in the region where the fusion interface is located through the notch feature data, and converging to generate the target size feature data and the target shape feature data.
[0008] Optionally, the step of performing wire cutting on the substrate surface based on the target size feature data to output a grooved substrate with a preset rectangular groove includes: parsing the target size feature data to obtain target width and target depth values; guiding the wire cutting device to perform a peeling action on the substrate surface based on the target width and target depth values to generate the preset rectangular groove; and using anhydrous ethanol reagent to perform washing and polishing actions on the surface of the preset rectangular groove to output the grooved substrate exhibiting the original gloss characteristics.
[0009] Optionally, the step of performing a single-layer multi-pass laser cladding operation based on the cleaned grooved substrate to guide the cladding material to bond with the sidewall of the preset rectangular groove and generate a clad part containing a laser cladding layer and a fusion interface includes: obtaining preset laser cladding process parameters that match the target material; performing a material filling operation inside the preset rectangular groove of the grooved substrate based on the preset laser cladding process parameters; guiding the liquid metal in the material filling operation to undergo a metallurgical bonding reaction with one sidewall of the preset rectangular groove to generate the fusion interface that presents an approximately vertical spatial distribution relative to the substrate surface, and outputting the clad part.
[0010] Optionally, the step of performing a positioning and cutting action on the cladding part based on the target shape feature data to output the micro-tensile specimen to be tested includes: performing a planar cutting action with the original surface of the grooved substrate as a spatial positioning reference to peel off and obtain a sheet-like cladding part; performing an ultrasonic oscillation cleaning action on the sheet-like cladding part using anhydrous ethanol reagent to filter out surface contaminants; performing a planarization action on the surface of the cleaned sheet-like cladding part using abrasive media, and performing a chemical etching action using an acidic alcohol solution to develop the boundary contour of the fusion interface; performing a contour processing action with the developed fusion interface as a spatial anchor point to generate the notch feature, and constraining the fusion interface to be positioned within the narrow area of the notch feature, and outputting the micro-tensile specimen to be tested.
[0011] Optionally, controlling the micro-area micro-tensile stage to perform tensile testing on the micro-tensile specimen under test based on an intermittent tensile strategy of alternating tensile and holding actions includes: extracting the minimum tensile speed parameter of the micro-area micro-tensile stage; configuring a first tensile time span parameter and a second holding time span parameter; performing a first-stage tensile action on the micro-tensile specimen under test based on the minimum tensile speed parameter and the first tensile time span parameter; maintaining the current stress state after the first-stage tensile action stops, and performing a second-stage static action based on the second holding time span parameter; alternately triggering the first-stage tensile action and the second-stage static action, so that the average test speed parameter over the entire cycle is lower than a preset real service speed threshold.
[0012] Optionally, the method further includes: sending a command to the scanning electron microscope to perform a micro-morphology capture action within the static time window of the second-order static action; extracting deformation feature data of crack initiation and crack propagation at the fusion interface based on the micro-morphology capture action; and collecting the deformation feature data to construct image data of the micro-fracture process for characterizing the entire fracture cycle.
[0013] Optionally, the step of simultaneously extracting load-displacement curve data and microscopic fracture process image data based on the scanning electron microscope includes: activating the image sensing component based on the preset imaging frequency parameter, continuously extracting and combining morphological evolution images to generate the microscopic fracture process image data; extracting the field of view magnification parameter and feature anchor point offset parameter; performing numerical conversion based on the field of view magnification parameter, the feature anchor point offset parameter, and the preset imaging frequency parameter to generate the true displacement value characterizing the plastic deformation region; and simultaneously extracting the real-time mechanical sensing values output by the loading system, and fitting the true displacement values to generate the load-displacement curve data.
[0014] Optionally, the step of performing mechanical and morphological analysis based on the load-displacement curve data and the microscopic fracture process image data to output interface mechanical property data and interface fracture failure mode data includes: retrieving inflection point coordinate values from the load-displacement curve data to extract yield strength parameters and ultimate fracture parameters, and mapping them to generate the interface mechanical property data; extracting cross-sectional texture features and crack propagation direction features from the microscopic fracture process image data; and comparing the cross-sectional texture features and crack propagation direction features with a preset failure case library to match and output whether the interface fracture failure mode data belongs to a pure brittle fracture state classification or a pure ductile fracture state classification.
[0015] Compared with the prior art, the present invention has the following advantages: 1. Using a micro-area tensile stage in the scanning electron microscope chamber for in-situ observation, the complete microscopic morphological evolution process from crack initiation to final fracture can be recorded in real time and continuously. This provides a real and reliable experimental method for analyzing interface failure mechanisms and exploring the physical process of laser cladding, breaking through the bottleneck of traditional macroscopic tensile testing that cannot capture microscopic dynamic fracture characteristics.
[0016] 2. By introducing a grooved substrate design with pre-set rectangular slots on the substrate surface, the traditional sampling method parallel to the substrate plane is changed. The positional relationship between the fusion interface and the substrate plane is adjusted to a near-perpendicular state, allowing a single-layer, multi-pass thin cladding layer to meet the dimensional requirements of the microscopic in-situ tensile specimen. This effectively avoids the cracks and voids that often occur when increasing thickness using traditional multi-layer cladding. While ensuring the quality stability of the test specimen, it reduces the consumption of substrate and cladding powder materials, saving preparation costs.
[0017] 3. An intermittent tensile strategy, alternating between tensile and load-holding actions, was introduced. By adjusting the loading steps of the micro-area micro-tensile stage and coordinating with the time ratio settings, the average testing speed throughout the cycle was effectively reduced, allowing it to accurately match the stress rate of the cladding interface during actual service. This not only effectively prevents instantaneous interface fracture and data distortion caused by excessive hardware-inherent loading speed, but also provides sufficient dynamic imaging time for scanning electron microscopy, ensuring clear capture of the underlying key microscopic features of crack propagation.
[0018] Other features and advantages of the invention will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing the invention. The objects and other advantages of the invention may be realized and obtained by means of the structures pointed out in the description, claims and drawings. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1 This is a schematic flowchart of a method for preparing and in-situ observing microscopic tensile fracture specimens at laser cladding interfaces according to an embodiment of the present invention.
[0021] Figure 2 This is a schematic diagram of the basic dimensions and shape of a microscopic in-situ tensile specimen, which is part of a method for preparing and observing microscopic tensile fracture specimens at a laser cladding interface according to an embodiment of the present invention.
[0022] Figure 3 A schematic diagram of the microscopic in-situ tensile specimen size design for a method of preparing and observing microscopic tensile fracture specimens at laser cladding interfaces according to an embodiment of the present invention.
[0023] Figure 4This is a schematic diagram of the microscopic in-situ tensile specimen sampling design for a method of preparing and observing microscopic tensile fracture specimens at the laser cladding interface according to an embodiment of the present invention.
[0024] Figure 5 This is a schematic diagram of the microscopic in-situ tensile specimen preparation process of a method for preparing and observing microscopic tensile fracture specimens at the laser cladding interface according to an embodiment of the present invention.
[0025] Figure 6 This is a schematic diagram of the microscopic in-situ sample assembly and field of view magnification of a method for preparing and observing microscopic tensile fracture samples at laser cladding interfaces according to an embodiment of the present invention.
[0026] Figure 7 This is a schematic diagram of the microscopic in-situ tensile load-displacement curve of a method for preparing and observing microscopic tensile fracture specimens at the laser cladding interface according to an embodiment of the present invention.
[0027] Figure 8 This is a schematic diagram of the in-situ tensile fracture failure process of a 42CrMo substrate sample, which is a method for preparing and observing the microscopic tensile fracture of a laser cladding interface according to an embodiment of the present invention.
[0028] Figure 9 This is a schematic diagram of the fracture morphology of the T15-42CrMo cladding interface, which is a method for preparing and in-situ observing microscopic tensile fracture specimens at the laser cladding interface according to an embodiment of the present invention. Detailed Implementation
[0029] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] Reference Figure 1 One embodiment of the present invention proposes a method for preparing and in-situ observing microscopic tensile fracture specimens at laser cladding interfaces. A single-layer multi-pass laser cladding is performed on a grooved substrate with a preset rectangular groove to construct a clad part containing a fusion interface. Based on the target shape features, a microscopic tensile specimen to be tested with a notch feature associated with the fusion interface is cut out in the middle. In-situ loading is performed by controlling a micro-area micro-tensioning stage through an intermittent tensioning strategy that alternates between tensioning and holding actions. This method can overcome the limitations of single-layer cladding thickness and reduce material costs, while capturing the complete microscopic evolution process of crack initiation, propagation and fracture at the laser cladding fusion interface.
[0031] The method described in this embodiment specifically includes: Extract the load range parameters and dimensional requirements of the microscopic in-situ tensile testing equipment, and extract the tensile property data of the material to be tested; Based on the load range parameters, the size requirement parameters, and the tensile performance data, target size feature data and target shape feature data of the micro tensile specimen are constructed. Based on the target size feature data, a wire cutting operation is performed on the substrate surface to output a grooved substrate with a preset rectangular groove; A cleaning operation is performed on the preset rectangular groove of the grooved substrate, and a single-layer multi-pass laser cladding operation is performed on the cleaned grooved substrate to guide the cladding material to bond with the sidewall of the preset rectangular groove, thereby generating a clad part containing a laser cladding layer and a fusion interface. Based on the target shape feature data, a positioning and cutting action is performed on the cladding part to output a micro tensile specimen to be tested, wherein the middle position of the micro tensile specimen to be tested has a notch feature associated with the fusion interface. The control clamping device assembles the micro tensile specimen to be tested into the micro-area micro tensile stage in the scanning electron microscope, and performs the device configuration action based on the preset maximum load parameters and preset imaging frequency parameters. The micro-area micro-tensile stage is controlled to perform tensile testing on the micro-tensile specimen under test based on an intermittent tensile strategy that alternates between tensile action and load holding action, and load-displacement curve data and micro fracture process image data are extracted simultaneously based on the scanning electron microscope. Based on the load-displacement curve data and the microscopic fracture process image data, mechanical and morphological analysis is performed to output interface mechanical property data and interface fracture failure mode data.
[0032] Specifically, the load range parameters and dimensional requirements of the microscopic in-situ tensile testing equipment, as well as the tensile performance data of the test sample material, are extracted to construct target size feature data and target shape feature data. Based on the target size feature data, a grooved substrate with a preset rectangular groove is processed on the substrate surface, and a single-layer multi-pass laser cladding action is performed in the cleaned preset rectangular groove to guide the cladding material to bond with the sidewall to form a clad part containing a fusion interface. Based on the target shape feature data, a positioning and cutting action is performed on the clad part to output a microscopic tensile specimen with a notch feature related to the fusion interface in the middle position. The clamping equipment is controlled to assemble the test specimen into the micro-area micro-tensile stage in the scanning electron microscope, and the test action is performed based on the intermittent tensile strategy of alternating tensile action and load holding action. Load displacement curve data and microscopic fracture process image data are extracted simultaneously based on the scanning electron microscope. Finally, the analysis action is performed to output interface mechanical property data and interface fracture failure mode data. By constructing grooves on the substrate surface and guiding the bonding of a single-layer multi-pass laser cladding layer with the sidewalls, the inherent technical barrier of being unable to prepare standard micro-tensile specimens due to the limited thickness of the single-layer cladding layer was successfully broken. This mechanism avoids the defects caused by the superposition of multiple additive manufacturing layers while reducing material consumption and specimen preparation costs. Combined with the intermittent loading test mode of alternating tensile and holding load actions, the average tensile speed throughout the entire cycle was actively controlled and reduced to closely match the actual physical stress state of the interface. This not only eliminated the instantaneous fracture distortion error caused by excessive continuous loading speed, but also reserved a stable dynamic imaging range for the micro microscope. As a result, high-fidelity in-situ capture and accurate mechanical determination of the deformation characteristics of the laser cladding interface from crack initiation to fracture were achieved.
[0033] Optionally, the step of constructing target size characteristic data and target shape characteristic data of the microscopic tensile specimen based on the load range parameter, the size requirement parameter, and the tensile property data includes: Extract the required fracture load parameters based on the tensile property data; Adjust the cross-sectional thickness value so that the fracture load parameter matches the preset proportional node of the load range parameter; Based on the aforementioned size requirement parameters, construct the feature data of the assembly positioning circular holes located on both sides; Based on the fracture load parameters, the notch feature data located in the middle position is constructed, so as to constrain the fracture position to be in the region where the fusion interface is located through the notch feature data, and the target size feature data and the target shape feature data are generated by combining them.
[0034] Specifically, the required fracture load parameters are extracted based on tensile property data. The theoretical load boundary required to break the interface is determined by obtaining the interfacial bonding strength of the test sample material. Next, the cross-sectional thickness is adjusted to match the fracture load parameters with a preset proportional node of the load range parameters. By changing the sample thickness, the stress-bearing cross-sectional area is controlled, ensuring that the dynamic load at fracture is within a safe and highly accurate measurement range. Subsequently, based on dimensional requirements, feature data of the assembly positioning circular holes on both sides are constructed to match the fastening drive shaft of the micro-area micro-tensile stage. Finally, based on the fracture load parameters, feature data of the notch in the middle position is constructed. The abrupt change in geometric dimensions induces a large stress concentration effect, forcing the deformation and fracture core region to be precisely confined at the fusion interface between the laser cladding layer and the substrate. This process generates target size feature data and target shape feature data. An adaptive control formula for cross-sectional thickness is introduced. ; h is the cross-sectional thickness in millimeters; The preset proportional node is a dimensionless constant, based on the vibration-resistant safety factor of the electron microscope vacuum chamber. This is the load range parameter, in Newtons; denoted as σa, the interfacial tensile strength, in megapascals (MPa); σb is the width of the narrowest notch, in millimeters. (Combined) Figure 2 The basic dimensions and shape design of the microscopic in-situ tensile specimen reveal that the overall specimen's topology and geometric parameters are constrained by the physical assembly space of the in-situ tensile apparatus. The relative positions and dimensions of the mounting and positioning holes on both sides are fixed to ensure rigid clamping, while the notch feature in the central area is directly related to the location of the cladding interface. Through precise scaling and shape control of these geometric dimensions, the fracture physical action can be ensured to occur uniquely and stably at the fusion interface, thus providing a prerequisite for subsequent microscopic dynamic observation.
[0035] For example, a laser cladding interface formed by blocky T15 high-speed steel powder and a 42CrMo steel substrate was constructed and tested. The selected micro-tensile stage had a fixed load range parameter of 1000 Newtons. The interfacial tensile strength of this material combination was known to be 1000 MPa based on previous metallurgical tensile benchmark tests. To ensure that the deformation of the sample during tensile testing was within the focusing field of view of the scanning electron microscope's electron beam, the width of the narrowest notch was set to 0.8 mm, based on the limits of wire cutting micromachining. To meet the safety requirements of protecting the internal components of the scanning electron microscope's vacuum chamber from vibration damage caused by the instantaneous release of elastic energy from sample fracture, the preset proportional node was set to an empirical safety value of 0.40. The thickness was then accurately calculated using a thickness adaptive control formula; the derivation process is as follows: The calculated section thickness is then set to 0.5 mm. The verification process for the corresponding required fracture load parameters is as follows: The theoretical load at fracture was determined to be 400 Newtons, which falls at the 40% mark of the 1000 Newton full-scale range, conforming to the vibration-resistant safety design of the vacuum chamber. Based on this data, a target dimensional feature was constructed with a total length of 26 mm, a width of 6 mm, and 3.1 mm diameter mounting and positioning holes on both sides, symmetrically distributed at a distance of 4 mm from the end. A symmetrical arc notch with a radius of 1.5 mm was constructed in the middle, with the distance from the central axis of the two arc notches to the left end of the specimen controlled at 13 mm to ensure its coincidence with the internal fusion interface geometry. After processing, the microscopic tensile specimen was placed in the fixture, and the tensile test was initiated. The sensor recorded the actual fracture load as 400 Newtons in real time. Figure 3 The dimensional preparation results of the microscopic in-situ tensile failure specimens of the cladding interface between the above-mentioned T15 high-speed steel powder and 42CrMo steel substrate, as well as the in-situ tensile control specimens of 42CrMo steel alone, are presented, which intuitively reflect the physical morphological characteristics of the interface located in an extremely narrow region.
[0036] Optionally, the step of performing wire cutting on the substrate surface based on the target size feature data to output a grooved substrate with a preset rectangular groove includes: The target size feature data is analyzed to obtain the target width and target depth values; Based on the target width and target depth values, the wire cutting device is guided to perform a peeling action on the substrate surface to generate the preset rectangular groove; The surface of the preset rectangular groove is washed and polished using anhydrous ethanol reagent, resulting in a grooved substrate that exhibits its original gloss characteristics.
[0037] Specifically, by reading the target size feature data, key grooving control parameters are extracted, and the target width and depth values of the preset rectangular groove are calculated. Then, a wire cutting machine is guided to perform high-precision electrical discharge machining on the substrate surface, driving an extremely fine metal wire to peel away the substrate metal along a set geometric trajectory, thereby precisely eroding and peeling out the preset rectangular groove of the designed specifications on the substrate. After the groove is formed, in order to remove the coolant and metal chips remaining from the cutting process, anhydrous ethanol is poured to fill the entire inner surface of the preset rectangular groove, and high-purity abrasive media is used to uniformly polish its sidewalls and bottom, destroying and peeling away the dense oxide layer that is instantaneously formed on the surface during the heating process, until all processing stains are removed and the grooved substrate with its original luster is exposed. The formula for controlling the geometric dimensions of the preset rectangular groove is introduced: ; ; In the formula, The target width value for the preset rectangular groove, in millimeters; The target distribution width of the laser cladding layer in the sample is expressed in millimeters. It is a non-uniformity compensation constant for the overlapping edges of multiple cladding passes, with the unit being millimeters. It is an empirical geometric correction coefficient, based on the average lateral span of the collapsed area at the first and last overlapping edges of the cladding passes. The target depth value for the preset rectangular groove, in millimeters; This represents the required effective cladding depth across the cross-section of the cladding layer, in millimeters. This is the thickness allowance for wire EDM machining, expressed in millimeters. It is a machining loss correction factor, based on the sum of the diameter of the molybdenum wire and the discharge gap during a single wire EDM step when subsequently peeling off the thin sheet sample.
[0038] For example, a 42CrMo steel substrate with dimensions of 100 mm, 100 mm, and 12 mm was used as the processing object to reproduce the grooving process. The effective melt depth requirement of the laser cladding layer cross-section in the middle of the sample was set. The thickness allowance for wire EDM is 1.0 mm, calculated based on the characteristics of the wire EDM process, the molybdenum wire diameter, and the discharge gap. The value is 0.3 mm according to the machine tool's factory standard. Simultaneously, based on the sample layout plan, the target distribution width of the laser cladding layer within the sample is determined. The constant is set to 15 mm to compensate for the unevenness of the overlapping edges of multiple cladding layers. Based on the statistical values of edge collapse morphology from multiple cladding stacking processes, a diameter of 2.5 mm was set. Then, the target width and depth of the preset rectangular groove were calculated using the geometric dimension adjustment formula. The specific calculation process for the target width is as follows: The calculated target width of the preset rectangular groove is 20 mm. The specific calculation process for the target depth is as follows: The target depth of the pre-defined rectangular groove was calculated to be 1.3 mm. Based on the calculated target width of 20 mm and the target depth of 1.3 mm, a fast wire EDM machine was guided to perform electrical erosion on the surface of a 42CrMo steel substrate along a longitudinal length of 100 mm, successfully peeling off the pre-defined rectangular groove with dimensions of 100 mm, 20 mm, and 1.3 mm. After the groove was formed, anhydrous ethanol reagent with a purity of 99.9% was poured into the inner surface of the groove, and the pre-defined rectangular groove was manually and uniformly ground from all sides with 400-grit silicon carbide sandpaper to remove the micron-level adhering deterioration layer caused by high-temperature electrical discharge cutting, until a clean and bright silver-white substrate surface was exposed inside the groove. This resulted in a groove-shaped substrate with an output surface exhibiting the original luster characteristics, providing a standard interface for the defect-free metallurgical bonding of subsequent cladding materials.
[0039] Optionally, the single-layer multi-pass laser cladding process performed on the cleaned grooved substrate, guiding the cladding material to bond with the sidewall of the preset rectangular groove to generate a clad part including a laser cladding layer and a fusion interface, includes: Obtain the preset laser cladding process parameters that match the target material; Based on the preset laser cladding process parameters, a material filling action is performed inside the preset rectangular groove of the grooved substrate; The liquid metal in the material filling process is guided to undergo a metallurgical bonding reaction with one side wall of the preset rectangular groove to generate the fusion interface that presents an approximately vertical spatial distribution relative to the substrate surface, and the cladding part is output.
[0040] Specifically, preset laser cladding process parameters matching the target material are obtained. These core parameters include key physical variables that determine heat input and forming quality, such as laser power, scanning speed, and spot diameter. Based on these preset laser cladding process parameters, material filling is performed inside a preset rectangular groove on a grooved substrate. A high-energy laser beam is used to instantly melt the synchronously fed alloy powder, forming a single-layer, multi-pass cladding entity spread along the bottom of the groove. During the cladding process, the overlap between the laser beam spot edge and the sidewall of the preset rectangular groove is precisely controlled to guide the liquid metal generated during the material filling process to undergo a deep metallurgical bonding reaction with one sidewall of the preset rectangular groove. As the high-energy heat source is removed, the liquid metal rapidly solidifies, thereby generating a fusion interface that is approximately vertically distributed relative to the substrate surface. Finally, a clad part containing the laser cladding layer and the fusion interface is output outward. To precisely control the fusion quality of the sidewall, a formula for the sidewall heat input energy density is introduced: ; The symbols in the formula are given digital interpretations. ρ represents the sidewall heat input energy density, in joules per square millimeter; k is the sidewall beam overlap compensation constant, dimensionless, based on the statistical average energy loss of the laser on a high-reflectivity metal vertical sidewall; P is the laser output power, in watts; V is the laser scanning speed, in millimeters per second; d is the laser spot diameter, in millimeters. Figure 4 A comparison of microscopic in-situ tensile specimen sampling designs reveals that traditional sampling methods require extremely large cross-sectional areas and thicknesses of the cladding layer, which not only easily induces multilayer stacking defects but also results in material waste. This solution completely changes the conventional sampling approach parallel to the substrate plane by introducing a grooved substrate. This sampling design spatially alters the near-parallel relationship between the fusion interface and the substrate plane from almost parallel to a near-vertical distribution, successfully achieving stable acquisition of standard microscopic tensile specimens spanning the interface even under extremely thin single-layer, multi-pass cladding conditions, thus eliminating the thickness dimension bottleneck in additive manufacturing.
[0041] For example, the technical reproduction is carried out by filling a pre-defined rectangular groove in a grooved substrate made of 42CrMo steel with T15 high-speed steel powder to form a clad part. To ensure that the sidewall of the pre-defined rectangular groove can be fully melted without large-area thermal collapse, based on the previous thermodynamic test data of the combination of T15 high-speed steel and 42CrMo steel, the target threshold for the sidewall heat input energy density is set to 60. Referring to the optical path reflection loss record table of the current equipment's laser generator, the sidewall beam overlap compensation constant is determined to be 0.85. The laser spot diameter is set to 2.0 and the laser scanning speed to 10. The laser output power is then derived in reverse using the configuration parameters; the known derivation formula is transformed as follows: The process of performing calculations and derivations by substituting specific parameters is as follows: Based on the hardware characteristics of the equipment's hundreds-digit step accuracy, the laser output power was rounded down to 1412. Using these preset laser cladding process parameters, the coaxial powder-feeding laser cladding machine was started to fill the material inside a preset rectangular groove. High-temperature liquid metal spread closely against one side wall of the preset rectangular groove. Under a high-power directional heat input of 1412 watts, the side wall surface underwent micro-melting to a depth of 0.2 mm and violently reacted with the liquid metal in a metallurgical bonding process. After cooling and solidification, a near-vertical spatial distribution with an 89-degree angle between the fusion interface and the substrate's horizontal plane was successfully generated, ultimately producing a composite clad part with a high-strength vertical interface.
[0042] Optionally, the step of performing a positioning and cutting action on the cladding part based on the target shape feature data to output the microscopic tensile specimen to be tested includes: Using the original surface of the grooved substrate as a spatial positioning reference, a planar cutting operation is performed to peel off and obtain a sheet-like clad part; The sheet-like cladding parts were cleaned by ultrasonic oscillation using anhydrous ethanol to remove surface contaminants. The surface of the cleaned sheet-like cladding part is smoothed using abrasive media, and chemical etching is performed using an acidic alcohol solution to reveal the boundary contour of the fusion interface. Using the developed fusion interface as a spatial anchor point, a contour processing operation is performed to generate the notch feature, and the fusion interface is constrained to be positioned within the narrow area of the notch feature, and the microscopic tensile specimen to be tested is output.
[0043] Specifically, using the original surface of the grooved substrate as a spatial positioning reference, a planar excision operation is performed. A precision wire cutting machine is used to cut parallel to the original upper surface of the substrate, peeling off a thin sheet-like cladding component containing the laser cladding layer and the substrate material. Anhydrous ethanol is used to perform ultrasonic cleaning on the sheet-like cladding component. The sheet-like cladding component is immersed in anhydrous ethanol, and an ultrasonic generator is activated to induce cavitation. The shock waves generated by the bursting of microbubbles filter out surface contaminants such as cutting fluid and oil. After cleaning, the surface of the cleaned sheet-like cladding component is smoothed using abrasive media. Gradually changing to finer grit sandpaper, the surface is polished until it achieves a mirror-like finish without obvious mechanical scratches. Finally, an acidic alcohol solution is used for chemical etching. The etching solution is evenly applied or dripped onto the polished surface. The difference in the etching rate of different microstructures to the acid is utilized to reveal the boundary contour of the fusion interface. Finally, using the developed fusion interface as a spatial anchor point, contour processing is performed, guiding the wire cutting equipment to cut the overall shape of the sheet-like cladding part according to the target shape feature data, generating a notch feature in the middle of the sample, and strictly constraining the fusion interface to be positioned within the narrow area of the notch feature, outputting a microscopic tensile sample that meets the requirements of dimensional accuracy and microstructure location: ; In the formula, The standard duration for chemical corrosion is expressed in seconds. This is a temperature compensation constant, dimensionless, based on the reaction kinetics correction benchmark under laboratory ambient temperature conditions. This represents the target development depth requirement, in micrometers. This refers to the mass fraction concentration of the acidic alcohol solution. It is the basic corrosion rate coefficient of the material, with units of micrometers per second, and is based on the statistical values of the dissolution of a specific metal in an acid solution of a unit concentration.
[0044] For example, a composite substrate made of T15 high-speed steel powder and a 42CrMo steel substrate was used as the sample for sampling and positioning processing. A wire cutting machine was started, using the original upper surface of the grooved substrate as a reference, and offset downwards by 0.5 mm to perform a planar removal operation, peeling off a sheet-like cladding piece with a length of 40 mm, a width of 8 mm, and a thickness of 0.5 mm. It was then immersed in an ultrasonic cleaning tank containing anhydrous ethanol reagent and cleaned at a frequency of 40 kHz for 10 minutes. After cleaning, a planarization operation was performed using silicon carbide wet sandpaper ranging from 400 to 2000 grit, followed by mechanical polishing to a mirror finish using diamond polishing paste with a particle size of 1 micrometer. Subsequently, a chemical etching operation was performed using a 0.004% nitric acid alcohol solution. To accurately control the development quality, a target development depth of 1.2 micrometers was set. Referring to the kinetics manual at laboratory room temperature (25 degrees Celsius), the temperature compensation constant was determined to be 1.05. Tests showed that the material-based corrosion rate coefficient of 42CrMo steel in nitric acid reagent was 15. The process of performing calculations and derivations based on the standard chemical corrosion time formula, by substituting data, is as follows: The calculated standard time for chemical corrosion was 21 seconds. The polished surface was wiped with a cotton swab soaked in a nitric acid-alcohol solution of this concentration for 21 seconds, then immediately rinsed with flowing anhydrous ethanol and dried. At this point, a clear boundary line between silver-white and dark gray was visible on the sample surface, representing the fusion interface after development. The sheet-like clad part was then re-clamped onto a high-precision wire EDM machine. The machine's microscope camera was aligned with this boundary line and set as the coordinate system anchor point. Using this anchor point as the center reference, contour machining was performed to remove excess edge material and create semi-circular notches with radii of 1.5 mm on both sides. This ensured that the physical geometric center line of the narrowest region (only 0.8 mm wide) coincided with the developed boundary line, ultimately outputting a high-precision microscopic tensile specimen. Figure 5 This demonstrates the entire physical morphology evolution of the sample, from precisely cutting grooves on the substrate surface, performing single-layer multi-pass laser cladding, obtaining thin sheets, to finally exposing the fusion interface through chemical etching and fine polishing, and processing a standard notched sample.
[0045] Optionally, controlling the micro-area micro-tensile stage to perform tensile testing on the micro-tensile specimen based on an intermittent tensile strategy that alternates between tensile and load-holding actions includes: Extract the minimum tensile speed parameters of the micro-area micro-stretching stage; Configure the first tensile time span parameter and the second load holding time span parameter; The first-order tensile action is performed on the microscopic tensile specimen to be tested based on the hardware minimum tensile speed parameter and the first tensile time span parameter. After the first-stage stretching action stops, the current stress state is maintained, and the second-stage static action is performed based on the second load-holding time span parameter; Alternating the first-stage stretching action with the second-stage stationary action results in the average test speed parameter for the entire cycle being lower than the preset actual service speed threshold.
[0046] Specifically, the minimum tensile speed parameters of the micro-area micro-tensile stage are extracted, and the lower limit of the physical rate at which the motor can stably output is obtained by reading the underlying driver of the tensile equipment. Based on the testing requirements and the exposure time needed for microscope imaging, the first tensile time span parameters and the second holding time span parameters are configured. Then, based on the minimum tensile speed parameters and the first tensile time span parameters, the first-order tensile action is performed on the microscopic tensile specimen under test, causing a small and constant displacement of the fixture. After the first-order tensile action stops, the current stress state is maintained, and the second-order static action is performed based on the second holding time span parameters, during which the specimen strain remains physically locked. By alternately triggering the first-order tensile action and the second-order static action through the control system, and utilizing a discontinuous pressurization method in the time domain, the average test speed parameter over the entire cycle is kept below the preset real service speed threshold. ; In the formula, This is the average test speed parameter, in micrometers per second; This is the minimum stretching speed parameter for hardware, expressed in micrometers per second. This is the first stretching time span parameter, in seconds; This is the second load-bearing time span parameter, in seconds.
[0047] For example, a certain version of the micro-area micro-tensile stage was used to reproduce the intermittent in-situ test of a composite micro-tensile specimen composed of T15 high-speed steel and 42CrMo steel. Referring to the equipment's underlying operation manual, the minimum tensile speed parameter was found to be 3.3 micrometers per second. Based on the fracture analysis measurement report of the T15 high-speed steel interface under actual service conditions, the safe critical loading rate for actual micro-fracture at the interface was determined. Using this data, a preset actual service speed threshold of 1.5 micrometers per second was set. To ensure that the average test speed parameter is strictly below this threshold and to meet the requirement that the electron microscope requires at least 2.0 seconds of stabilization time to complete a single image scan, the first tensile time span parameter was set to 1.0 second, and the second holding time span parameter was set to 2.3 seconds. The microscopic tensile specimen is secured at both ends in a micro-tensile stage. The control system drives the motor to smoothly stretch the specimen to both sides at a speed of 3.3 micrometers per second for 1.0 second to perform the first stage of tensile action. The motor is then de-energized and stops, and the mechanical components self-lock to maintain the current tensile displacement for 2.3 seconds to perform the second stage of static holding. The calculation and derivation process based on the equivalent velocity control model is as follows: The calculated average test speed parameter for the entire alternating cycle was precisely 1.0 micrometers per second. This result of 1.0 micrometers per second meets the core requirement of a real service speed threshold below 1.5 micrometers per second. The equipment continuously and alternately triggered 1.0-second tensile and 2.3-second hold-load operations until the middle part of the microscopic tensile specimen under test physically fractured, successfully acquiring mechanical response and deformation evolution data without high-speed distortion at a rate matching the operating conditions.
[0048] Optionally, the method further includes: Within the static time window of executing the second-order static action, a command is sent to the scanning electron microscope to execute the microscopic morphology capture action; Based on the micromorphological capture action, deformation feature data of crack incubation and crack propagation at the fusion interface are extracted; The deformation feature data are collected to construct image data of the microscopic fracture process to characterize the entire fracture cycle.
[0049] Specifically, within the static time window during which the motor of the micro-area tensile stage stops operating and the axial displacement of the sample is locked, a signal command is immediately sent to the communication interface of the high-resolution scanning electron microscope to trigger the electron gun beam deflection coil inside the microscope to perform microscopic morphology capture. As the electron beam scans line by line within a specific field of view, the image acquisition system synchronously receives the electrical signal fed back from the secondary electron detector. Based on the dramatic changes in grayscale contrast within the feedback signal, it extracts two-dimensional deformation feature data of crack initiation and propagation caused by material tearing in the local area of the fusion interface. As multiple static cycles alternate during the intermittent tensile test, the storage unit serializes and collects the two-dimensional deformation feature data with independent timestamps acquired in each independent static stage according to time sequence, thereby constructing image data that can characterize the microscopic fracture process of the interface from stress to breakage like a continuous animation. A static time window safety verification formula is introduced: ; In the formula, This is the lower limit of the static time window safety value, in seconds; The horizontal pixel resolution of the image, in pixels; The vertical pixel resolution of the image, in pixels; The electron beam scanning rate is measured in pixels per second and is based on the hardware limitation of the highest sampling frequency of the electron microscope's digital-to-analog converter. This is the device communication delay constant, measured in seconds. It is based on the combined time consumed by the physical data cable transmission and digital instruction parsing between the industrial control computer and the microscope motherboard.
[0050] For example, after the technical reproduction verification of the fracture observation of the composite sample of T15 high-speed steel and 42CrMo steel on the micro-area micro-tensile stage, a trigger imaging command is sent to the scanning electron microscope after entering the static load holding stage. To ensure that the electron microscope can obtain a clear fracture morphology without motion blur, the static time window safety calculation formula is introduced for pre-execution verification. The horizontal pixel resolution of the image to be extracted for observation is set to 1024 pixels, and the vertical pixel resolution of the image is also 1024 pixels. According to the hardware performance specification manual of the equipment, the electron beam scanning rate is set to one million pixels per second. The equipment communication delay constant is determined according to the industrial serial communication protocol standard and fixed at 0.2 seconds. The calculation derivation process of the execution safety lower limit time is 1024 multiplied by 1024 divided by one million, plus 0.2, which calculates to a basic microscopic scanning time of 1.048576 seconds. The sum of the two results in a final static time window safety lower limit value of 1.248576 seconds. The static holding time set in the preliminary configuration was 2.3 seconds, which covers and exceeds the theoretical safety lower limit of 1.248576 seconds. Within this 2.3-second static window, the microscope successfully completed line-by-line electron beam scanning, accurately extracting local micro-regions where the grayscale contrast of the metal bonding area showed significant darkening and jumps, i.e., the underlying deformation characteristic data of crack initiation and propagation. The system software automatically stored a frame of deformation characteristic image after each alternating stretching and holding cycle, and seamlessly arranged and combined hundreds of images acquired throughout the tensile fracture process according to the timestamp generation order, ultimately successfully outputting a complete and high-definition image sequence stream demonstrating the dynamic microscopic fracture process of a micron-level metal crack from initiation to complete breakage. Figure 6 The images show the actual assembly and clamping state of the specimen inside the micro-tense stage during the intermittent tensile test, as well as the characteristic field images of the local fracture process captured by scanning electron microscopy at different magnifications.
[0051] Optionally, the simultaneous extraction of load-displacement curve data and microscopic fracture process image data based on the scanning electron microscope includes: Based on the preset imaging frequency parameters, the image sensing component is activated to continuously extract and combine morphological evolution images to generate the micro fracture process image data. Extract the field magnification parameter and the feature anchor point offset parameter; Based on the field magnification parameter, the feature anchor point offset parameter, and the preset shooting frequency parameter, a numerical conversion operation is performed to generate a true displacement value representing the plastic deformation region. The real-time mechanical sensing values output by the loading system are extracted synchronously, and the load-displacement curve data is generated by fitting the actual displacement values.
[0052] Specifically, based on preset image capture frequency parameters, the image sensing component is activated, and the instrument's built-in image acquisition software continuously extracts images of the morphological evolution of the surface of the microscopic tensile specimen at fixed time intervals. These discrete two-dimensional images are then combined and arranged to generate image data characterizing the entire dynamic failure cycle of the microscopic fracture process. The magnification parameter of the current microscopic observation field is extracted, and the feature anchor point offset parameters of specific microstructural spots are extracted by comparing adjacent frames using a digital image correlation algorithm. Based on the magnification parameter, feature anchor point offset parameters, and preset image capture frequency parameters, numerical conversion is performed, converting digital pixel displacements into real displacement values characterizing the plastic deformation region through the principle of optical geometric mapping. Simultaneously, real-time mechanical sensing values output by the micro-area micro-tensile stage are extracted, and combined with the real displacement values obtained above, a two-dimensional coordinate system is fitted to generate load-displacement curve data for interface mechanical analysis.
[0053] ; In the formula, The actual displacement value is in millimeters; T is the total duration of the tensile test, in seconds. The preset shooting frequency parameter is in Hertz, and it is set according to the lower limit of the time resolution required to accurately capture the transient propagation of microcracks. This is the feature anchor point offset parameter between two adjacent image frames, in pixels; is the reference pixel physical equivalent constant of the electron microscope sensor, with the unit being millimeters per pixel. It is based on the absolute physical geometric size of a single pixel of the photosensitive element inside the microscope; M is the field of view magnification parameter, which is a dimensionless constant.
[0054] For example, the technical reproduction verification was performed using the load-displacement curve data of the T15 and 42CrMo steel cladding interface sample (number #2). During the in-situ microscopic tensile test, the preset imaging frequency was set to 5 Hz to meet the requirements of continuous dynamic capture. The magnification parameter of the electron microscope was adjusted and locked to 300x to clearly observe local microscopic morphological features. Referring to the manufacturer's hardware manual for this tensile testing microscope, the reference pixel physical equivalent constant of the electron microscope sensor was determined to be 0.003 mm per pixel. The total duration of the tensile test was recorded as 20 seconds. After the test stopped, the image processing algorithm extracted the average value of the feature anchor point offset parameter between two adjacent frames during the plastic deformation stage, which was 20 pixels. The system then performed the calculation and derivation process for the actual displacement value by extracting the total number of frames. The derivation of the calculation of physical displacement in a single frame is as follows: The actual displacement value is obtained by summing the physical displacement values of each of the 100 frames. At the physical moment corresponding to the recorded 0.02 mm displacement value, the real-time mechanical sensing value of the loading output was simultaneously extracted as 265 Newtons, indicating that the sample had just undergone micro-yielding at this time. Using the derived 0.02 mm as the horizontal axis displacement data and the corresponding 265 Newtons as the vertical axis load data, a two-dimensional coordinate point at the yielding moment was generated. This pixel calculation and mechanical matching process was repeated throughout the entire cycle, ultimately fitting and outputting a complete load-displacement curve data for determining whether the material belongs to a brittle or ductile fracture mode. Figure 7 The data compares the actual load-displacement curves generated by visually tracking displacement through the above images and extracting it using mechanical sensing. This clearly shows the differences in the mechanical response characteristics of samples of different materials during the yielding and fracture stages.
[0055] Optionally, the mechanical and morphological analysis performed based on the load-displacement curve data and the microscopic fracture process image data, and the output of interface mechanical property data and interface fracture failure mode data, include: The yield strength parameter and ultimate fracture parameter are extracted by retrieving the inflection point coordinate values from the load-displacement curve data, and then mapped to generate the interface mechanical property data. Extract cross-sectional texture features and crack propagation direction features from the microscopic fracture process image data; Based on the comparison between the cross-sectional texture features and the crack propagation direction features, a pre-set failure case library is used to match and output whether the interface fracture failure mode data belongs to the pure brittle fracture state classification or the pure ductile fracture state classification.
[0056] Specifically, the load-displacement curve data obtained from tensile test records is analyzed. By finding the coordinates of the first physical inflection point where the slope of the curve decreases and deviates from the linear elastic proportional stage, the yield strength parameter and its corresponding yield displacement value are extracted. Then, the highest physical tensile peak point on the curve is found, and the ultimate fracture parameter and its corresponding ultimate fracture displacement value are extracted. These four key mechanical indicators reflecting the material's intrinsic strength are aggregated and mapped to generate interface mechanical property data. Pixel information is extracted from continuously captured microscopic fracture process images. Using digital image edge detection and gray-level co-occurrence matrix algorithms, the microscopic undulations of the fracture surface, i.e., the cross-sectional texture features, are extracted. The angle between the macroscopic extension trajectory of the main crack and the horizontal plane of the test specimen, i.e., the crack extension direction feature, is extracted using Hough linear transform. The extracted mechanical displacement ratio and morphological angle values are substituted into the brittle-ductile determination function for calculation. The calculated quantitative results are compared with the empirical determination threshold in a pre-set failure case library. Based on the numerical range, the fracture mechanism of the target material is classified as either a purely brittle fracture state or a purely ductile fracture state. The brittle-ductile determination function formula is introduced: ; In the formula, It is a brittleness-toughness index, which is a dimensionless constant. The value represents the ultimate fracture displacement, in millimeters. This is the yield displacement value, in millimeters; It is the numerical value of the angle between the crack propagation direction and the cross-section of the specimen, in degrees. It is based on the solid mechanics fracture criterion that the direction of the most intense shear deformation of a metallic material under axial tension forms a 45-degree angle with the cross-section. The calculation is performed using a sine trigonometric function. The preset threshold for the brittle-ductile boundary is set to 1.0, which is based on the empirical critical product of the elongation rate during the plastic deformation stage and the shear angle, obtained from a large number of fracture surface micro-metallographic tests.
[0057] For example, firstly, the mechanical curve of specimen No. 1 is analyzed, and its physical inflection point coordinates are extracted to obtain the yield strength parameter of 290 Newtons and the corresponding yield displacement value of 0.12 mm. The highest peak point is then identified, from which the ultimate fracture parameter of 400 Newtons is extracted and the corresponding ultimate fracture displacement value of 0.277 mm is extracted. Subsequently, image processing algorithms are used to analyze the fracture photograph of specimen No. 1, identifying that the cracks mainly run horizontally and evenly. Image recognition measurements show that the angle between the crack extension direction and the specimen cross-section is 5 degrees. Substituting these core parameters into the brittle-ductile criterion function, the calculation derivation process for specimen No. 1 is as follows: The calculated judgment index of 0.227 was compared with the threshold of 1.0 in the preset failure case library. Since 0.227 is less than the threshold of 1.0, the interface fracture failure mode data of the first sample was accurately matched and classified as a pure brittle fracture state. As a control verification, data of the pure substrate control sample was extracted, and its ultimate fracture displacement was found to be 1.153 mm and its yield displacement was found to be 0.200 mm. The presence of a large and obvious shear lip region was identified using image visual features, and its principal angle was measured to be 45 degrees. The calculation derivation process performed simultaneously on the control sample is as follows: Since 4.765 is greater than the set threshold of 1.0, the bilinear calculation conclusion of the failure mode classification of the automatically matched control group as a pure ductile fracture state is consistent with the metallographic section experimental results verified by manual physical verification, fully verifying the discrimination accuracy of the quantitative analysis method and the underlying algorithm formula. Figure 8 and Figure 9 The dynamic extension process of ductile fracture failure of pure substrate extracted from in-situ observation and the micromorphology of brittle instantaneous fracture of interface composite sample are respectively shown. The shear fracture characteristics and normal stress fracture characteristics of both fully confirm the calculation conclusions of the above failure mode classification.
[0058] It should be noted that the electrical connections between the various units described above do not necessarily represent direct or indirect connections. Any indirect connection method can be applied to the embodiments of the present invention as long as it achieves the purpose of the present invention. The above descriptions are merely exemplary embodiments of the present invention and should not be construed as limiting the scope of the present invention.
[0059] All equivalent changes and modifications made in accordance with the teachings of this invention are still within the scope of this invention. Those skilled in the art will readily conceive of other embodiments of this invention upon considering the specification and the disclosure of practical truth. This application is intended to cover any variations, uses, or adaptations of this invention that follow the general principles of this invention and include common knowledge or conventional techniques in the art not described herein.
Claims
1. A method for preparing and in-situ observing microscopic tensile fracture specimens at laser cladding interfaces, characterized in that, include: Extract the load range parameters and dimensional requirements of the microscopic in-situ tensile testing equipment, and extract the tensile property data of the material to be tested; Based on the load range parameters, the size requirement parameters, and the tensile performance data, target size feature data and target shape feature data of the micro tensile specimen are constructed. Based on the target size feature data, a wire cutting operation is performed on the substrate surface to output a grooved substrate with a preset rectangular groove; A cleaning operation is performed on the preset rectangular groove of the grooved substrate, and a single-layer multi-pass laser cladding operation is performed on the cleaned grooved substrate to guide the cladding material to bond with the sidewall of the preset rectangular groove, thereby generating a clad part containing a laser cladding layer and a fusion interface. Based on the target shape feature data, a positioning and cutting action is performed on the cladding part to output a micro tensile specimen to be tested, wherein the middle position of the micro tensile specimen to be tested has a notch feature associated with the fusion interface. The control clamping device assembles the micro tensile specimen to be tested into the micro-area micro tensile stage in the scanning electron microscope, and performs the device configuration action based on the preset maximum load parameters and preset imaging frequency parameters. The micro-area micro-tensile stage is controlled to perform tensile testing on the micro-tensile specimen under test based on an intermittent tensile strategy that alternates between tensile action and load holding action, and load-displacement curve data and micro fracture process image data are extracted simultaneously based on the scanning electron microscope. Based on the load-displacement curve data and the microscopic fracture process image data, mechanical and morphological analysis is performed to output interface mechanical property data and interface fracture failure mode data.
2. The method for preparing and in-situ observing microscopic tensile fracture specimens at laser cladding interfaces according to claim 1, characterized in that, The process of constructing target size characteristic data and target shape characteristic data of the microscopic tensile specimen based on the load range parameter, the size requirement parameter, and the tensile property data includes: Extract the required fracture load parameters based on the tensile property data; Adjust the cross-sectional thickness value so that the fracture load parameter matches the preset proportional node of the load range parameter; Based on the aforementioned size requirement parameters, construct the feature data of the assembly positioning circular holes located on both sides; Based on the fracture load parameters, the notch feature data located in the middle position is constructed, so as to constrain the fracture position to be in the region where the fusion interface is located through the notch feature data, and the target size feature data and the target shape feature data are generated by combining them.
3. The method for preparing and in-situ observing microscopic tensile fracture specimens at laser cladding interfaces according to claim 1, characterized in that, The step of performing wire cutting on the substrate surface based on the target size feature data to output a grooved substrate with a preset rectangular groove includes: The target size feature data is analyzed to obtain the target width and target depth values; Based on the target width and target depth values, the wire cutting device is guided to perform a peeling action on the substrate surface to generate the preset rectangular groove; The surface of the preset rectangular groove is washed and polished using anhydrous ethanol reagent, resulting in a grooved substrate that exhibits its original gloss characteristics.
4. The method for preparing and in-situ observing microscopic tensile fracture specimens at laser cladding interfaces according to claim 1, characterized in that, The single-layer multi-pass laser cladding process is performed on the cleaned grooved substrate to guide the cladding material to bond with the sidewall of the preset rectangular groove, generating a clad part including a laser cladding layer and a fusion interface. Obtain the preset laser cladding process parameters that match the target material; Based on the preset laser cladding process parameters, a material filling action is performed inside the preset rectangular groove of the grooved substrate; The liquid metal in the material filling process is guided to undergo a metallurgical bonding reaction with one side wall of the preset rectangular groove to generate the fusion interface that presents an approximately vertical spatial distribution relative to the substrate surface, and the cladding part is output.
5. The method for preparing and in-situ observing microscopic tensile fracture specimens at laser cladding interfaces according to claim 1, characterized in that, The step of performing a positioning and cutting action on the cladding part based on the target shape feature data, and outputting a micro tensile specimen to be tested, includes: Using the original surface of the grooved substrate as a spatial positioning reference, a planar cutting operation is performed to peel off and obtain a sheet-like clad part; The sheet-like cladding parts were cleaned by ultrasonic oscillation using anhydrous ethanol to remove surface contaminants. The surface of the cleaned sheet-like cladding part is smoothed using abrasive media, and chemical etching is performed using an acidic alcohol solution to reveal the boundary contour of the fusion interface. Using the developed fusion interface as a spatial anchor point, a contour processing operation is performed to generate the notch feature, and the fusion interface is constrained to be positioned within the narrow area of the notch feature, and the microscopic tensile specimen to be tested is output.
6. The method for preparing and in-situ observing microscopic tensile fracture specimens at laser cladding interfaces according to claim 1, characterized in that, The method of controlling the micro-area micro-tensile stage to perform tensile testing on the micro-tensile specimen under test based on the intermittent tensile strategy of alternating tensile and load-holding actions includes: Extract the minimum tensile speed parameters of the micro-area micro-stretching stage; Configure the first tensile time span parameter and the second load holding time span parameter; The first-order tensile action is performed on the microscopic tensile specimen to be tested based on the hardware minimum tensile speed parameter and the first tensile time span parameter. After the first-stage stretching action stops, the current stress state is maintained, and the second-stage static action is performed based on the second load-holding time span parameter; Alternating the first-stage stretching action with the second-stage stationary action results in the average test speed parameter for the entire cycle being lower than the preset actual service speed threshold.
7. The method for preparing and in-situ observing microscopic tensile fracture specimens at laser cladding interfaces according to claim 6, characterized in that, The method further includes: Within the static time window of executing the second-order static action, a command is sent to the scanning electron microscope to execute the microscopic morphology capture action; Based on the micromorphological capture action, deformation feature data of crack incubation and crack propagation at the fusion interface are extracted; The deformation feature data are collected to construct image data of the microscopic fracture process to characterize the entire fracture cycle.
8. The method for preparing and in-situ observing microscopic tensile fracture specimens at laser cladding interfaces according to claim 1, characterized in that, The simultaneous extraction of load-displacement curve data and microscopic fracture process image data based on the scanning electron microscope includes: Based on the preset imaging frequency parameters, the image sensing component is activated to continuously extract and combine morphological evolution images to generate the micro fracture process image data. Extract the field magnification parameter and the feature anchor point offset parameter; Based on the field magnification parameter, the feature anchor point offset parameter, and the preset shooting frequency parameter, a numerical conversion operation is performed to generate a true displacement value representing the plastic deformation region. The real-time mechanical sensing values output by the loading system are extracted synchronously, and the load-displacement curve data is generated by fitting the actual displacement values.
9. The method for preparing and in-situ observing microscopic tensile fracture specimens at laser cladding interfaces according to claim 1, characterized in that, The mechanical and morphological analysis performed based on the load-displacement curve data and the microscopic fracture process image data outputs interface mechanical property data and interface fracture failure mode data, including: The yield strength parameter and ultimate fracture parameter are extracted by retrieving the inflection point coordinate values from the load-displacement curve data, and then mapped to generate the interface mechanical property data. Extract cross-sectional texture features and crack propagation direction features from the microscopic fracture process image data; Based on the comparison between the cross-sectional texture features and the crack propagation direction features, a pre-set failure case library is used to match and output whether the interface fracture failure mode data belongs to the pure brittle fracture state classification or the pure ductile fracture state classification.